Evaluation of biomechanical movements and injury risk factors in weight lifting (snatch) - Moon, Y. J. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to investigate the possibility of injuries and the types of movement related to damage by body parts, and to prepare for prevention of injuries and development of a training program. Method: For this study, the experiment was conducted according to levels of 60 percentages (ST) and 85 percentages (MA) and 10 subjects from the Korean elite national weightlifting team were included. Furthermore, we analyzed joint moment and muscle activation pattern with three-dimensional video analysis. Ground reaction force and EMG analyses were performed to measure the factors related to injuries and motion. Results: Knee reinjuries such as anterior cruciate ligament damage caused by deterioration of the control ability for the forward movement function of the tibia based on the movement of the biceps femoris when the rectus femoris is activated with the powerful last-pull movement. In particular, athletes with previous or current injuries should perceive a careful contiguity of the ratio of the biceps femoris to the rectus femoris. This shows that athletes can exert five times greater force than the injury threshold in contrast to the inversion moment of the ankle, which is actively performed for a powerful last pull motion and is positively considered in terms of intentional motion. It is activated by excessive adduction and internal rotation moment to avoid excessive abduction and external rotation of the knee at lockout motion. It is an injury risk to muscles and ligaments, causing large adduction moment and internal rotation moment at the knee. Adduction moment in the elbow joint increased to higher than the injury threshold at ST (60% level) in the lockout phase. Hence, all athletes are indicated to be at a high risk of injury of the elbow adductor muscle. Lockout motion is similar to the "high five" posture, and repetitive training in this motion increases the likelihood of injuries because of occurrence of strong internal rotation and adduction of the shoulder. Training volume of lockout motion has to be considered when developing a training program. Conclusion: The important factors related to injury at snatch include B/R rate, muscles to activate the adduction moment and internal rotation moment at the elbow joint in the lockout phase, and muscles to activate the internal rotation moment at the shoulder joint in the lockout phase.